Enhancing the Performance of Building Integrated Photovoltaic Systems (BIPVs) Using High Efficient Power Modules - Kamala Kannan, N.; Ramesh, S. M. (Asian Journal of Electrical Sciences, 2018)
A Building Integrated Photovoltaic Systems (BIPV) consists of PV modules which are integrated in to the Buildings as facades, roofs, windows, etc., The Photovoltaic PVs are mainly implemented to convert the solar irradiance in to electrical energy. These building integrated PVs are placed in different orientations and angles. However, due to the variation of the solar irradiance, temperature and also due to mismatch of electrical parameters the performances of the BIPV systems are getting affected. Also Power configurations are becomes difficult, which leads to reduced reliability and energy efficiency. Hence, this paper intends to introduce high efficient DC-DC converter by implementing a novel enemy to friend optimization algorithm technique with the use of MPPT. Initially, the solar irradiance obtained by the solar panel is converted into DC by using the Maximum Power Point Tracking (MPPT). In which, the Pulse Width Modulation (PWM) is generated based on the optimization process, for this purpose, an E2F algorithm is implemented. In this technique, the enemy who has the minimum anger (i.e. the duty cycle which has the minimum value) is selected and then make it as a friend. The output power obtained after implementing the DC-DC converter is given as the input for inverter. Finally the output of the inverter is connected to Grid or Load. In simulation, the efficiency of the proposed power module with DC – DC converter is evaluated and analyzed using the measure of those outputs with varying temperature.